Exposure to plastic debris alters expression of biomineralization, immune, and stress-related genes in the eastern oyster (Crassostrea virginica). - Laura E Eierman; Jacob Landis (PLoS ONE)
The degradation of marine plastic debris poses a threat to organisms by fragmenting into micro- and nano-scale pieces and releasing a complex chemical leachate into the water. Numerous studies have investigated harms from plastic pollution such as microplastic ingestion and exposure to single chemicals. However, few studies have examined the holistic threat of plastic exposure and the synergistic impacts of chemical mixtures. The objective of this study was to measure changes in gene expression of gill and gonadal tissue of the eastern oyster (Crassostrea virginica) in response to plastic debris exposure during their first year, using RNA-seq to explore multiple types of physiological responses. Shell and polyethylene terephthalate plastic were used as substrate for the metamorphosis of larval oysters in a settlement tank. Substrate pieces were then transferred to metal cages and outplanted in pairs - shell cage and plastic cage - onto restoration reefs in the St. Mary's River, Maryland, USA. After 10 months of growth, the oysters were collected, gill and gonadal tissue removed, and sex identified. The tissues of six oysters from each sex and substrate type were then analyzed in RNA-seq. Both gill and gonadal tissue samples had altered expression of immune and stress-response genes in response to plastic exposure. Genes upregulated in response to plastic were enriched for gene ontology functions of proteolysis and fibrinolysis. Downregulated genes were involved in shell biomineralization and growth. One male oyster exposed to plastic had "feminized" gene expression patterns despite developing mature sperm, suggesting plastic leachate can alter gene expression and shift protandric individuals to develop as females. Plastic pollution may therefore reduce shell growth, initiate immune and stress responses, alter sex differentiation, and impact reproductive output of eastern oysters through changes in transcription.